Larval settlement and metamorphosis of Mytilus coruscus in response to varying bacterial capsular polysaccharide - He, Chu-Han; Zhang, Wen; Hu, Xiao-Meng; Yoshida, Asami; Osatomi, Kiyoshi; Liang, Xiao; Yang, Jin-Long (Frontiers in Marine Science, 2023)
Marine invertebrates are the backbone of marine biodiversity and play a pivotal role in the marine ecosystem. The life cycle of most marine invertebrates includes the settlement and metamorphosis stage, which is induced by marine biofilms, but the mechanism is still enigmatic. In the present study, we constructed the capsular polysaccharide (CPS) synthesis gene capC-deleted mutant of Pseudoalteromonas marina by gene knockout and then compared the phenotype, the biofilm-forming ability, the effect on settlement and metamorphosis of Mytilus coruscus, and the exopolysaccharide and CPS levels between the mutant and the wild-type strains to explicate the relationship between bacteria and mussels. The study presented that the phenotype and biofilm-forming ability between the wild-type and ΔcapC strains had no significant difference, but the inducing activity of ΔcapC biofilms on larval settlement and metamorphosis decreased significantly (p < 0.05). Compared with the wild-type, the CPS content of ΔcapC strain significantly decreased by 38.07%, accompanied by the increase of c-di-GMP. Meanwhile, the biomass of α-polysaccharides and β-polysaccharides on ΔcapC biofilms decreased significantly (p < 0.05). Thus, the CPS synthesis gene could modulate c-di-GMP, which regulates bacterial polysaccharide secretion, and then impact larval settlement and metamorphosis of mussels. This work brings an entry point to deeply understand the interaction between bacterial polysaccharide and larval recruitment.